The sorrows of gin - Hofsiss, Jack; Wasserstein, Wendy; Herrmann, Edward, 1943-2014; Weaver, Sigourney, 1949-; Hobel, Mara; Cheever, John (Cheever, John. Short stories., 1979)
This tale of life in suburban America centers on an eight year old girl's search for a sense of family amid the sophisticated and detached whirl of her parents' lives. The little girl's efforts to deal with alienation and emotional isolation lead her to run away from home.